Explaining the Brexit Referendum: The Role of Worker Skill Level in Voter Decisions. - Park, Youngduek; Kim, Yongmin (Political Quarterly, 2018)
On 23 June 2016, the UK's 'Brexit' referendum saw a majority vote to leave the EU—a result that shocked the world. Using European Social Survey data, we argue that Brexit was not simply decided by less‐educated voters who did not understand the EU's value. Pro‐Brexit votes were determined by economic interests as well as emotional, psychological, and attitudinal factors related to European integration. We demonstrate that skill level played a more important role in voter decision than education, gender, age, and political stance.